2009
DOI: 10.1097/nrl.0b013e31817781b6
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in Metabolic Syndrome

Abstract: Our results demonstrate that migraine prevalence in metabolic syndrome was higher than in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 35 publications
(27 reference statements)
7
74
1
Order By: Relevance
“…The results of the study demonstrated that increased waist circumference, obesity, and impaired glucose metabolism, which are components of metabolic syndrome, were more frequent in patients with migraine. Insulin resistance was suggested to be responsible for high migraine prevalence because it is common in the pathogenesis of these disorders (32). A study evaluated 83 patients with episodic migraine patients, 83 patients with chronic migraine, and 83 healthy individuals, and BMI, waist circumference, and blood pressure measurements were performed.…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…The results of the study demonstrated that increased waist circumference, obesity, and impaired glucose metabolism, which are components of metabolic syndrome, were more frequent in patients with migraine. Insulin resistance was suggested to be responsible for high migraine prevalence because it is common in the pathogenesis of these disorders (32). A study evaluated 83 patients with episodic migraine patients, 83 patients with chronic migraine, and 83 healthy individuals, and BMI, waist circumference, and blood pressure measurements were performed.…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…Migraineurs are much more likely to have metabolic disorders than non-migraineurs [23][24][25][26][27][28][29] which we speculated is connected to carbohydrate disturbance of electrolytes [30]. Additionally, migraineurs have only nominal changes in voltage between states of action potential versus resting potential, indicating that a migraine brain is "always on," [31,32] supporting the theory that migraineurs have hyper sensitive sensory organs [33,34].…”
Section: Introductionmentioning
confidence: 56%
“…The extracranial terminal branches of the external carotid artery were suspected to be the reason of pain in the aura [11,12]. Newer data imply that migraine headache is caused by an inappropriate activation of trigeminovascular system, that is, pain sensitive innervation of dural, arachnoid, and pial vessels as well as large intracranial vessels by nociceptive fibers originating in trigeminal ganglion (TG) and travelling mainly through ophthalmic and to a much lesser extent through maxillary and mandibular divisions of trigeminal nerve [10,13,14]. Appropriately, "neurovascular disorder" definition has been used to address dysfunction of the cerebral nerves and blood vessels through cortical activation which is followed by brainstem activation with neurogenic inflammation and vasodilation [15][16][17].…”
Section: Pathophysiology Of Migrainementioning
confidence: 99%